Merengkuh Kerapuhan: Pendampingan Dan Konseling Pastoral Terhadap Pemuda Sandwich Generation Yang Mengalami Gangguan Kecemasan Di Jemaat GMIM Imanuel Toraget Wilayah Langowan Dua - Nadia Lumintang; Maria E. Tulangouw (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
This article highlights the reality of young people in the GMIM Imanuel Toraget congregation who live under pressure as the sandwich generation, a group bearing a double burden in meeting the needs of their parents, siblings, and themselves. Economic pressures, family responsibilities, and the lack of emotional and spiritual support cause anxiety that affects their life balance and participation in church life. The purpose of this study is to explain the factors causing anxiety among sandwich generation youth, describe the church’s response to their struggles, and explore appropriate and contextual forms of pastoral care and counseling. This research employs a qualitative descriptive method through interviews, observations, and theological reflection. The results are expected to provide a foundation for the church to develop empathetic and relevant pastoral ministry that helps young people build faith resilience amid life’s complex pressures.